G498(P) Are we failing our children and our future? introducing medical students to child health inequalities. (27th April 2015) - Morrissey, B; Powell, P; Moreiras, J
Abstract : Background and aims: Huge inequalities exist in child health globally. Current under five mortality rates vary significantly between countries from 2.3 per 1000 live births in Singapore to 152.5 per 1000 live births in Guinea-Bissau. In the UK, children from poorer socio-economic backgrounds are more likely to be born small, die during their first year of life and die from an accident in childhood. We aimed to develop and evaluate a student-selected component (SSC) introducing medical students to inequalities in child health. Methods: The student-selected component (SSC) ran one afternoon a week for eight weeks. Students participated in four interactive workshops on topics around child inequality and attended a relevant paediatric clinic or service. Students completed a self-directed project exploring an area of possible inequality for children, produced a poster and gave a short presentation at the end of the SSC, which was assessed. We evaluated the SSC by e-mailing a structured questionnaire to all participants and analysed responses thematically. Results: Twelve second year students undertook the SSC. All 12 completed the post-programme questionnaire. Medical students gained the following from participating in the SSC: An increased understanding of the inequalities that exist in child health. "I was quite shocked at how large the differences were especially within the UK. Research and presentation skills. An awareness of the need for effective interventions to reduce inequality and improve children's health. " It's not just a matter of throwing money towards services for children but preventing the inequalities from happening in the first place." An increased motivation to see the situation improve. " This has fired me up to want to do something about this in the future." Seven out of 12 students (58%) reported that doing the SSC had either confirmed or increased their desire to pursue paediatrics as a career. Three further students reported they had wanted to do paediatrics before doing the SSC. Conclusions: Introducing medical students to child health inequalities early on in their undergraduate training can have significant benefits, particularly in helping students to understand the broader social determinants of health, and encouraging more medical students to take up careers in child health.